The effects of Genistein on osseointegration of Titanium implants in experimental ovariectomized model - Uzun, Cansu Busra; Dundar, Serkan; Kom, Mustafa; Yildirim, Tuba Talo; Bozoglan, Alihan; Balci, Tansel Ansal; Şahin, Kazım (Univ Zulia, Facultad Ciencias Veterinarias, 2025)
Osseointegration is a challenge in the dental implant treatment of individuals with osteoporosis. Genistein is a phytoestrogen with beneficial effects in the prevention of osteoporosis. This study aims to evaluate the protective effects of genistein supplementation on the osseointegration level of titanium implants in ovariectomized rats. The rats in this study were randomly divided into 5 groups with 8 rats in each group: Control, Implant, Ovariectomy-Implant, Ovariectomy-Implant-Genistein, Implant-Genistein. The implants were surgically integrated tibial bones of rats. Genistein was administered at 2 mgkg-1 by oral gavage three times a week. All rats were sacrificed at the end of 3 months. Biochemical analyses were made from the blood serum of the rats, histomorphometric analyses from the implant and surrounding tissues placed in the tibia, and bone mineral density analyses from the mandibles. The bone implant connection (BIC) ratio of the Control-Implant group was higher than the other groups (P<0.05). The BIC ratio of the Ovariectomy-Implant group was lower than the Ovariectomy-Implant-Genistein and Implant-Genistein groups (P<0.05). In terms of thread filling, no statistically significant difference was found between the groups (P>0.05). The jaw bone mineral density (BMD) of the control group was higher than the Ovariectomy-Implant and Implant-Genistein groups (P<0.05). In ovariectomy-Implant-Genistein group jaw BMD was higher than the Ovariectomy-Implant and Implant-Genistein groups (P<0.05). In conclusion, it can be stated that genistein can improve the negative effects of ovariectomy on the bone and increase implant osseointegration. Genistein consumption may increase implant osseointegration in osteoporotic cases.
Efectos de la Genisteína en la oseointegración de implantes de Titanio en un modelo experimental ovariectomizado
Keywords: Osseointegration; ovariectomy; osteoporosis; phytoestrogen; genistein